Restorative Justice in the Digital Era: Criminal Law Mediation Through Online Platforms - Saida Flora, Henny; Aspan, Henry (PT. Anagata Sembagi Education, 2025)
The paradigm transformation of criminal law enforcement from a retributive to a restorative approach reflects a response to the weaknesses of the conventional justice system that is rigid, slow, and lacks space for victim recovery. Restorative justice (RJ), as a dialogue-based and reconciliation-based approach, has been accommodated in Indonesian law through the SPPA Law and several other administrative regulations. However, the adoption of this approach in general criminal cases and its implementation online still faces serious legal challenges. This study uses a normative juridical method to examine the urgency of regulating digital-based criminal mediation (restorative justice digital/RJD) within the framework of the national criminal law system. The study focused on the limitations of the applicable positive law, the validity of the results of online mediation, the protection of personal data, and the potential for inequality of access for vulnerable groups. The findings show that without comprehensive and integrative regulation with the principle of due process of law, the implementation of the RJD risks violating constitutional rights and undermining the legitimacy of restorative justice itself. Therefore, it is necessary to synchronize criminal law norms, procedural law, the ITE Law, and the PDP Law to form an adaptive, inclusive, and accountable legal framework. The RJD can be a strategic innovation in criminal law reform, as long as it is carried out with legal certainty and strong human rights protection